Varicella Zoster Virus Reactivation Involving the Vagus Nerve. (July 2023) - Davis, Seth; Thomas, Evan; Lowery, Anne; Kahue, Charissa; Gelbard, Alexander
Objectives: To characterize the presentation, clinical course and functional outcomes of patients with varicella zoster virus (VZV) reactivation involving the vagus nerve. To highlight the role of otolaryngology in acute and long-term management of laryngopharyngeal VZV and its sequelae. Methods: Retrospective review of 3 patients with laryngopharyngeal VZV, managed at a tertiary referral center. Results: All cases presented with vesicular lesions involving mucosa of the laryngopharynx. Each experienced vocal fold hypomobility, among other otolaryngologic sequelae. All were treated with systemic antivirals and corticosteroids. Mucosal lesions resolved within 7 days of treatment initiation; functional deficits persisted for months to years. Dysphonia improved to a plateau at 3 months, while dysphagia took longer to resolve. One patient with disseminated disease experienced bilateral vocal fold paralysis requiring temporary tracheostomy. Conclusions: Vagal neuropathy secondary to VZV reactivation is a rare clinical entity with a variety of laryngeal manifestations. Early initiation of systemic therapy and serial endoscopic evaluations are critical components of acute management when laryngopharyngeal involvement is suspected. Otolaryngologists should plan for long-term phonatory and deglutitive therapy in these cases, as neurologic sequelae can persist for months to years following initial insult. Level of Evidence: Level 4 (Case-series).